Factors that Influence the Effectiveness of Sanitation Programs - Fernandez-Haddad, Marilu; Ingram, Maia (Frontiers in Public Health, 2015)
Local governments in both Mexico and the U.S. spend considerable money on public services, which do not always bring the expected results. For instance, a large part of the public budget is destined to solve social and health problems such as public sanitation. Government has attacked the problem by providing public sanitation infrastructure (such as garbage and recycling receptacles) and the use of social ad campaigns. However, these efforts do not always impact the habits of residents and bring the desired changes in city sanitation. This paper presents a case study that used a participatory method to address an innovative city sanitation effort: The Clean City Program in Puebla, Mexico. This program adopted social marketing techniques, a discipline born in the 70s when the principles and practices developed to sell products and services started to be applied to sell ideas, attitudes or behaviors. Social marketing programs have been adopted by governments to change attitudes and behavior in areas such as public services. The paper first describes the context and strategies of the program which included the use of the promotora model to engage community members. The researchers then make use of qualitative data gathered throughout program planning and implementation to evaluate the impact of the social marketing programs and its effectiveness. The paper analyses social, educational, economic, demographic and cultural factors that influence the effectiveness of sanitation programs and presents recommendations for strategies to engage community members in community sanitation programs.